White and gray matter damage in primary progressive MS: The chicken or the egg?. (12th January 2016) - Bodini, Benedetta; Chard, Declan; Altmann, Daniel R.; Tozer, Daniel; Miller, David H.; Thompson, Alan J.; Wheeler-Kingshott, Claudia; Ciccarelli, Olga
Abstract : Objective: The temporal relationship between white matter (WM) and gray matter (GM) damage in vivo in early primary progressive multiple sclerosis (PPMS) was investigated testing 2 hypotheses: (1) WM tract abnormalities predict subsequent changes in the connected cortex ("primary WM damage model"); and (2) cortical abnormalities predict later changes in connected WM tracts ("primary GM damage model"). Methods: Forty-seven patients with early PPMS and 18 healthy controls had conventional and magnetization transfer imaging at baseline; a subgroup of 35 patients repeated the protocol after 2 years. Masks of the corticospinal tracts, genu of the corpus callosum and optic radiations, and of connected cortical regions, were used for extracting the mean magnetization transfer ratio (MTR). Multiple regressions within each of 5 tract-cortex pairs were performed, adjusting for the dependent variable's baseline MTR; tract lesion load and MTR, spinal cord area, age, and sex were examined for potential confounding. Results: The baseline MTR of most regions was lower in patients than in healthy controls. The tract-cortex pair relationships in the primary WM damage model were significant for the bilateral motor pair and right visual pair, while those in the primary GM damage model were only significant for the right motor pair. Lower lesion MTR at baseline was associated with lower MTR in the same tract normal-appearing WM at 2 years in 3 tracts. Conclusion: These results are consistent with the hypothesis that in early PPMS, cortical damage is for the most part a sequela of normal-appearing WM pathology, which, in turn, is predicted by abnormalities within WM lesions.